2018
DOI: 10.2147/ijn.s167443
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PEG surface density and chain length on the pharmacokinetics and biodistribution of methotrexate-loaded chitosan nanoparticles

Abstract: BackgroundOne of the most important aspects of drug delivery is extended nanoparticle (NP) residence time in vivo. Herein, we report a series of methotrexate (MTX)-loaded chito-san (CS) NPs coated with differently sized methoxy polyethylene glycol (mPEG) at different mPEG surface densities.Materials and methodsMTX was incorporated into NPs (112.8–171.2 nm in diameter) prepared from the resulting mPEG-g-CS. The NPs had a zeta potential of +7.4–35.0 mV and MTX loading efficiency of 17.1%–18.4%. MTX/mPEG-g-CS NPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…for mPEG10K-zein), therefore demonstrating that PEGylation with a shorter PEG chain length could improve the cellular uptake efficacy of the zein micelles. Higher uptake with a shorter PEG chain length was consistent with several types of PEGylated nanocarriers [34,36,37]. Increasing PEG MW was shown to prevent nanoparticle-cell interactions, as higher MW PEG grafting led to a larger surface shielding of the micelles [38,39].…”
Section: Size and Zeta Potential Of Mpeg-zein Micelles In The Presenc...supporting
confidence: 62%
See 1 more Smart Citation
“…for mPEG10K-zein), therefore demonstrating that PEGylation with a shorter PEG chain length could improve the cellular uptake efficacy of the zein micelles. Higher uptake with a shorter PEG chain length was consistent with several types of PEGylated nanocarriers [34,36,37]. Increasing PEG MW was shown to prevent nanoparticle-cell interactions, as higher MW PEG grafting led to a larger surface shielding of the micelles [38,39].…”
Section: Size and Zeta Potential Of Mpeg-zein Micelles In The Presenc...supporting
confidence: 62%
“…The increased entrapment with the higher PEG MW was also observed in PEG-coated fluconazole nanoparticles [32]. However, in some delivery systems, such as PEG-PLGA and chitosan nanoparticles, the encapsulation efficiency was independent of the PEG MW [33,34]. It was even found to decrease with increasing PEG MW, for example, in the case of cholesterol-bearing PEGylated polymeric micelles, due to the overall low cholesterol content in the co-polymer chain for polymers with higher MW PEG, making these micelles less favorable for drug encapsulation [35].…”
Section: Characterization Of Mpeg-zein Micellesmentioning
confidence: 88%
“…Similarly, Bachir et al compared chitosan (MW 11 kDa) NPs conjugated with PEG at various degrees of substitution loaded with methotrexate having a particle size of about 110-171 nm and zeta potential +7-35 mV found that non-PEGylated chitosan NPs accumulated significantly in the liver and spleen at 24 h following intravenous administration and to a lower extent in lungs, kidneys, and heart. In contrast, PEGylated chitosan NPs distributed primarily to the kidneys [167]. Intraperitoneal injection of FITC-labeled carboxymethyl chitosan revealed similar high uptake in the liver of 300 kDa molecular weight chitosan, whereas unspecified chitosan degradation products of about 45 kDa were found in the urine [168].…”
Section: Effect Of Physical Properties On Biodistributionmentioning
confidence: 92%
“…Surface PEG conformation on nanoparticles has been shown to affect nanoparticle uptake by cells [36]. Several studies have shown that as PEG density increases on nanoparticles, uptake by macrophages and dendritic cells [37-42], as well as cancer cells [37, 43], is reduced. PEGylation appears to have differing results depending on the cell type – PEGylation reduces nanoparticle uptake by macrophages and dendritic cells, as indicated by studies demonstrating that PEG needed to be in a brush conformation to evade uptake and clearance by macrophages [41].…”
Section: Discussionmentioning
confidence: 99%